Exploring the use of POLY4 for the improvement of productivity, peanut quality, and soil properties in Southern India - Gopinath, Kodigal A.; Rajanna, Gandhamanagenahalli A.; Visha Kumari, Venugopalan; Singh, Vinod Kumar; Ajay, B. C.; Awasthi, Neeraj K.; Mishra, Vipin; Sukumaran, Suvana; Venkatesh, Govindarajan; Rajkumar, Bollam (Frontiers in Plant Science, 2024)
Polyhalite based POLY4, a multi-nutrient source containing potassium, calcium, magnesium, and sulfur, is increasingly recognized for its potential to improve crop yields and soil health in agricultural systems. It is also been considered as a feasible approach for addressing deficiency of potassium, calcium, and sulphur within a single application source. The present study aimed to investigate the impact of polyhalite based POLY4 application, either as a complete or partial substitute for traditional potassium fertilizer and gypsum supplement, on the enhancement of peanut (Arachis hypogaea ) growth and soil quality. An extensive field study was conducted from 2021 and 2022, employing ten distinct nutrient management treatments with three replications in a randomized complete block design. The findings of the study indicated that the application of polyhalite (POLY4) in conjunction with only NP fertilizers resulted in a higher yield advantage of around 150-200 kg ha -1 as compared to plots treated with NPK + gypsum (at 500 kg ha -1 ) and control plots. Application of polyhalite based fertilizer (POLY4) at a rate of 100% equivalent of K along with NP fertilizers resulted in a significant increase in pod yield by 5.3-12.8% over NPK + gypsum and control plots. Thus, enhanced crop yield led to increase of 4.88% gross returns and 4.28% net returns with the application of POLY4 (100%) + NP fertilizers over other treatments. Likewise, variable rates of conventional fertilizers along with POLY4 (100% recommended) +NP +gypsum atat310 kg/ha significantly enhanced linoleic acid content (38.5%), oleic acid content and oil content (48.1%) by reducing palmitic acid (11.96%) content in the groundnut seed. Interestingly, using POLY4 at the 50% recommended rate also resulted in yields that were comparable to those obtained with 100% NPK. Therefore, applying POLY4, a polyhalite fertilizer, in either a 100% or 50% equivalent of the essential K can be an effective way to increase the production of peanut crops and promote agricultural sustainability.